Penggunaan Bahasa Bugis dalam Interaksi Antar Siswa Kelas X SMA AL-IHSAN Lekopancing Kabupaten Maros - Nur Aisyah S.; Andi Agussalim; Hajrah Hajrah (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. This study aims to determine how the use of Bugis language in the interaction of class X students at SMA AL-IHSAN Lekopancing during the learning process and outside of learning hours (rest). The type of research used is descriptive qualitative. Data collection is done by observation. The data in this study are data obtained from utterances in the form of words, phrases and sentences conveyed by class X students of SMA AL-Ihsan Lekopancing when interacting with other students. The source of data in this study is when interacting at school using Bugis language. Research data collection techniques from observations or observations. The results of this study show that students can interact using Bugis when the interlocutor is also able to use Buginese, in addition, the use of language is also influenced by situational factors, namely students speak in what language, to whom, when, where. , and about what problem.Keywords: Usage, Language, Buginese